La lucha temporal entre el bloqueador central y el colocador en voleibol de alto nivel - Busca, B.; Febrer, J. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2012)
The aim of the present study was to analyze the temporal fight of the volleyball Spanish high-level setter and the opponent middle-blocker to get advantage in the attack construction situations and blocking, respectively. A frame-by-frame high-speed video sequences analysis was used to calculate temporal descriptive data from setting trajectories and the anticipatory behaviour of the middle-blocker. In addition, middle-blockers behaviours were analyzed according to temporal motor response proposed by Broker and Crawley (2001) in a similar task. There was some evidence that middle-blockers develop anticipated responses for 60,94% of the actions. Finally, the relationship with block effectiveness was analyzed.